The Relationship between Quality of Work Life and Demographic - Rao , Kaur; Arora, R.S.; Vashisht, A K (Gyan Management Journal, 2013)
Quality  of work life (QWL) is a muWfaceted concept implying concern for members of an organization.·-:·:
Keywords: Work life; work environment; personal relationship; decision making